2018
DOI: 10.1002/jcb.27548
|View full text |Cite
|
Sign up to set email alerts
|

BLACAT1 predicts poor prognosis and serves as oncogenic lncRNA in small‐cell lung cancer

Abstract: Bladder cancer-associated transcript 1 (BLACAT1) is a novel identified long noncoding RNA (lncRNA) in bladder cancer, and has been suggested to function as an oncogenic lncRNA in several types of human cancer. However, its involvement in the progression of small-cell lung cancer (SCLC) remained unknown. The aim of our study was to investigate the clinical value and biological function in SCLC. In our results, BLACAT1 expression was increased in SCLC tissues and cell lines compared with paired adjacent normal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…9 BLACAT1 high-expression acts as a poor outcome biomarker for overall survival in small-cell lung cancer. 10 Importantly, BLACAT1 elevates the oxaliplatinresistance of GC by enhancing ABCB1 protein expression through inhibiting miR-361. 11 However, the detailed mechanism of BLACAT1 on the occurrence and development of GC needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…9 BLACAT1 high-expression acts as a poor outcome biomarker for overall survival in small-cell lung cancer. 10 Importantly, BLACAT1 elevates the oxaliplatinresistance of GC by enhancing ABCB1 protein expression through inhibiting miR-361. 11 However, the detailed mechanism of BLACAT1 on the occurrence and development of GC needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been reported to regulate gene expression in various cancers. 22 JAK2, as an upstream of JAK2/STAT3 signaling pathway, was selected for its cellular function in tumors in accordance with the role of LINC00511. Besides, previous studies have showed that proteins involved in signaling pathways can affect the radioresistance of tumors.…”
Section: Linc00511 Regulates Jak2/stat3 Signaling Pathwaymentioning
confidence: 99%
“…Functionally, knockdown of BLACAT1 was found to attenuate cell proliferation, migration, invasion, and arrest G0/G1 cell cycle in SCLC cells. 29 Taken together, BLACAT1 could potentially serve as a novel prognostic predictor and therapeutic target for lung cancer patients ( Figure 1B).…”
Section: Blacat1 In Lung Cancermentioning
confidence: 90%